Barium vanadium silicate BaVSi2O7: a t2g counterpart of the Han purple compound - Vasiliev, A. N.; Volkova, O.; Zvereva, E.; Isobe, M.; Ueda, Y.; Yoshii, S.; Nojiri, H.; Mazurenko, V.; Valentyuk, M.; Anisimov, V.; Solovyev, I.; Klingeler, Rüdiger; et al. (Physical review. B, Condensed matter and materials physics, 2013)
By means of thermodynamic and magnetic resonance measurements the S = 1/2 dimer system BaVSi2O7 is characterized. A broad maximum in the temperature dependence of the magnetic susceptibility and a Schottky-type anomaly in the specific heat allows estimating the main exchange interaction within V4+-V4+ dimers as J=37±1 K. This estimation is confirmed by pulsed magnetic field measurements of the magnetization, which is evidenced by the field-induced singlet-triplet transition at about 27 T. Both X-band and high-field terahertz electron spin resonance data qualitatively agree with the results of the specific heat and magnetization measurements. The electronic structure calculations, by using local density approximation, indicate that the magnetic properties of BaVSi2O7 can be interpreted within the weakly interacting dimer model.